The Installation of Maximilian Oldrich of Kounic-Rietberg as the Moravian Land Captain (Theatrum historiae, 2025)
The Moravian Land Captain represented a leading figure who headed the Moravian royal tribunal and presided over the proceedings of the Land Diet and other provincial bodies. The path to this office was not an easy one. Candidates were required to meet high standards, and influential supporters at court were also indispensable. The pinnacle of this journey for the new captain was the ceremonial installation at the Land House in Brno. The aim of this study is to analyse the process of the Land Captain’s installation, from his selection to the subsequent celebrations.
Keywords: Moravian Land Captain; Maxmilián Oldřich of Kaunitz-Rietberg; Installation; Moravia; Brno; Nobility; Moravian Royal Tribunal; Ceremony; Ceremonial Entry; Fireworks